2002
DOI: 10.1055/s-2002-30186
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous Venous Graft with One-Stage Prepared Schwann Cells as a Conduit for Repair of Long Segmental Nerve Defects

Abstract: The use of autogenous venous graft with intraluminal injection of Schwann cells to enhance nerve regeneration of long segmental nerve defects was evaluated in a rabbit tibial nerve-repair model. Schwann cells were isolated from the excised rabbit tibial nerve by using the polylysine differential adhesion method. The cultured cells were identified by immunocytochemical labeling for S-100 protein. Tibial nerve defects in 4-cm segments were created in 24 animals, which were then divided into three groups. In Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 35 publications
(55 reference statements)
1
63
1
2
Order By: Relevance
“…Subsequent comparisons revealed superior axon regeneration in veins with transplanted Schwann cells. [29] However, Schwann cells are difficult to isolate and are expensive, making the use of minced nerve parts as shown in the present study a practical option.…”
Section: Discussionmentioning
confidence: 85%
“…Subsequent comparisons revealed superior axon regeneration in veins with transplanted Schwann cells. [29] However, Schwann cells are difficult to isolate and are expensive, making the use of minced nerve parts as shown in the present study a practical option.…”
Section: Discussionmentioning
confidence: 85%
“…Although initial reports focused on short gap repairs, 5,18,26 several substrates have been studied for their potential to heal large gap defects when supplemented with AGCs, including purified SCs. 1,6,7,9,11,12,16,17,27,28,34,37,38,[40][41][42]44 Berrocal et al demonstrated that adding autologous SCs suspended in serum to AGCs significantly enhanced the ability to bridge larger gap distances in sciatic nerve repair in rats. 3 Autologous SCs can be harvested from either a donor nerve or from the epicenter of the traumatized nerve ends in sharp injuries (propeller injury, gunshot wound, stab wound).…”
Section: Discussionmentioning
confidence: 99%
“…Hadlock et al (2000) and Mosahebi et al (2001) showed, in the rat, that SC transplantation inside different types of nerve conduit leads to the improvement of both quality and rate of axon regeneration. SC-seeded vein conduits proved also to be effective, in the rabbit, in bridging long nerve defects up to 4 cm (Zhang et al, 2002) and 6 cm (Strauch et al, 2001), whereas the use of the vein conduit alone in the same experimental conditions was ineffective.…”
Section: Tissue Engineering Of Peripheral Nervesmentioning
confidence: 95%